Neonatal Screening on Tandem Mass Spectrometry as a Powerful Tool for the Reassessment of the Prevalence of Underestimated Diseases in Newborns and Their Family Members: A Focus on Short Chain Acyl-CoA Dehydrogenase Deficiency - Messina, MariaAnna (Int J Neonatal Screen, 2020)
Early detection of disabling diseases, prior to clinical manifestations, is the primary goal of newborn screening (NS). Indeed, the required number of core and secondary conditions selected for screening panels is increasing in many countries. Furthermore, newborn screening can lead to diagnosis of maternal diseases such as vitamin B12 deficiency or 3-MethylcrotonylCoA-carboxylase deficiency (3MCC). NS became mandatory in Sicily in December 2017. Here we report NS data collected between December 2017 and April 2020. Our results show that tandem mass spectrometry is a powerful tool for discovery of underestimated disease in newborns and their family members. Our panel included short chain acyl-CoA dehydrogenase deficiency (SCADD). Here, we report that results of our investigation led to reassessment of SCADD prevalence in our population. The infant and adult patients diagnosed in our study had previously not shown overt symptoms.